2013
DOI: 10.1158/1940-6207.capr-12-0410
|View full text |Cite|
|
Sign up to set email alerts
|

New Perspectives of Curcumin in Cancer Prevention

Abstract: Numerous natural compounds have been extensively investigated for their potential for cancer prevention over decades. Curcumin, from Curcuma longa, is a highly promising natural compound that can be potentially used for chemoprevention of multiple cancers. Curcumin modulates multiple molecular pathways involved in the lengthy carcinogenesis process to exert its chemopreventive effects through several mechanisms: promoting apoptosis, inhibiting survival signals, scavenging reactive oxidative species (ROS), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(151 citation statements)
references
References 95 publications
3
142
0
6
Order By: Relevance
“…In prostate cancer tissues, people found up-regulation of human epidermal growth factor receptor 2 (HER2) (Sfanos et al, 2012), indicating that the MAPK pathway may play an important role. Also, inflammation-related molecule COX-2 may be over-expressed in prostate cancer, COX-2 can be a transcription factor involved in inflammation-mediated stem cell proliferation (Park et al, 2013) (mainly via prostaglandin E2 (PGE2) (Thanan et al, 2012;Dixon et al, 2013), while in turn, inhibition of COX-2 by lasiodin could down-regulate the MAPK signaling pathways , which finally reduced bladder carcinogenesis (Thanan et al, 2012). The p38 MAPK signaling is proved to be essential in inflammation, perhaps by regulating the function of macrophages (Yang et al, 2014), in some of these cancers, cytokine IL-6 and IL6-R which function in activation of inflammatory and androgen receptor (AR) are up-regulated (Sfanos et al, 2012).…”
Section: Mapk and Prostate Cancermentioning
confidence: 99%
“…In prostate cancer tissues, people found up-regulation of human epidermal growth factor receptor 2 (HER2) (Sfanos et al, 2012), indicating that the MAPK pathway may play an important role. Also, inflammation-related molecule COX-2 may be over-expressed in prostate cancer, COX-2 can be a transcription factor involved in inflammation-mediated stem cell proliferation (Park et al, 2013) (mainly via prostaglandin E2 (PGE2) (Thanan et al, 2012;Dixon et al, 2013), while in turn, inhibition of COX-2 by lasiodin could down-regulate the MAPK signaling pathways , which finally reduced bladder carcinogenesis (Thanan et al, 2012). The p38 MAPK signaling is proved to be essential in inflammation, perhaps by regulating the function of macrophages (Yang et al, 2014), in some of these cancers, cytokine IL-6 and IL6-R which function in activation of inflammatory and androgen receptor (AR) are up-regulated (Sfanos et al, 2012).…”
Section: Mapk and Prostate Cancermentioning
confidence: 99%
“…The anticancer effects of curcumin have been widely studied, and it is regarded as a promising drug candidate for the treatment and prevention of cancer (22). It is considered that the mechanism underlying the anticarcinogenic effects of curcumin involves the induction of cancer cell apoptosis via regulation of the expression of anti-oncogenes, oncogenes and the cell cycle (22).…”
Section: A B D E F Cmentioning
confidence: 99%
“…It is considered that the mechanism underlying the anticarcinogenic effects of curcumin involves the induction of cancer cell apoptosis via regulation of the expression of anti-oncogenes, oncogenes and the cell cycle (22). However, previous studies have revealed that curcumin is able to inhibit cancer cell invasion and metastasis via signaling changes.…”
Section: A B D E F Cmentioning
confidence: 99%
“…Many in vitro and in vivo studies have shown that curcumin possesses antiinflammatory, antioxidant, and anticancer activity [61][62][63]. Recent studies have demonstrated that curcumin could alter the expression level of several miRNAs through epigenetic regulation.…”
Section: Epigenetic Regulation Of Mirnas By Curcuminmentioning
confidence: 99%